2011
DOI: 10.1130/g32259.1
|View full text |Cite
|
Sign up to set email alerts
|

How nonlinear is the creep deformation of polar ice? A new field assessment

Abstract: Most analyses of glacial systems require a relationship between strain rates and stresses for ice deforming in creep. For conditions relevant to glacier fl ow, much evidence shows that strain rates increase approximately as deviatoric stress raised to a power n. Field and laboratory experiments suggest that n ≈ ≈ 3, but values span a wide range and controversy persists. Most fi eld efforts to determine n seek clarity by examining situations with simple stress states. We instead use a fully three-dimensional mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…While our observations focus on regions that make up about a quarter of the extent of the ice shelves and experience stresses of order 100 kPa (Supplement Figure S4), complementary laboratory work showing that n = 4 is suitable at higher stresses [10] supports extending our conclusion that n ≈ 4 to other dynamic regions in Antarctica. Additionally, our conclusion complements a growing body of work advocating for the use of n > 3 in other areas of the cryosphere [13,14]. Taken together, this work calls for a broader community effort to quantify the uncertainties in the flow law parameters and the consequences of these uncertainties on models of glacier dynamics.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…While our observations focus on regions that make up about a quarter of the extent of the ice shelves and experience stresses of order 100 kPa (Supplement Figure S4), complementary laboratory work showing that n = 4 is suitable at higher stresses [10] supports extending our conclusion that n ≈ 4 to other dynamic regions in Antarctica. Additionally, our conclusion complements a growing body of work advocating for the use of n > 3 in other areas of the cryosphere [13,14]. Taken together, this work calls for a broader community effort to quantify the uncertainties in the flow law parameters and the consequences of these uncertainties on models of glacier dynamics.…”
supporting
confidence: 68%
“…Glen's Flow Law (Eq. 1) with n = 3 shows broad consistency with sparse observations of natural ice flows such as borehole deformation measurements and ice flow velocities, as well as laboratory experiments on polycrystalline ice aggregates under conditions relevant for ice sheets [6,10,[12][13][14][15][16][17][18][19][20]. However, nearly 70 years after its introduction, the need remains to test and rigorously calibrate the parameters n and A in the natural environment.…”
supporting
confidence: 57%
“…‘Glen's law’ (Glen, 1958) describes the relation between deviatoric stress ( σ ) and strain-rate ( ) by a power law with a stress exponent, n : This law is based on the maximum strength that is reached during secondary creep. In most studies, it is assumed that n = 3, although values ranging from 1 to 5 have also been reported, for example, based on experiments (Goldsby and Kohlstedt, 2001) and observations on ice sheets (Cuffey and Kavanaugh, 2011; Gillet-Chaulet and others, 2011). The pre-exponential factor depends on temperature ( T ), but also on the microstructure ( μs ), in particular the LPO.…”
Section: Introductionmentioning
confidence: 99%
“…In most studies, it is assumed that n = 3, although values ranging from 1 to 5 have also been reported, for example, based on experiments (Goldsby and Kohlstedt, 2001) and observations on ice sheets (Cuffey and Kavanaugh, 2011;Gillet-Chaulet and others, 2011). The pre-exponential factor depends on temperature (T), but also on the microstructure (μs), in particular the LPO.…”
Section: Flow Of Polar Ice Sheetsmentioning
confidence: 99%
“…Creep of finer grain size ice will have a larger contribution from grain size‐sensitive mechanisms (Goldsby, ; Faria et al ., ): the rheology of ice will vary with grain size. Grain size‐sensitive rheologies can be constrained in the laboratory and there is evidence of involvement of these rheologies in ice sheets (Cuffey & Kavanaugh, ) and the interiors of icy moons in the outer solar system (Barr & McKinnon, ; Durham et al ., ). Furthermore, a composite rheology that involves both grain size‐sensitive and grain size‐insensitive flow laws (Goldsby, ) fits natural data.…”
Section: Ebsd Data From Water Icementioning
confidence: 99%